PEMANFAATAN REAL TIME DATABASE UNTUK APLIKASI BERBASIS LOKASI - Erna Kumalasari Nurnawati; Rochmad Suseno; Muhammad Sholihul Masnuh; Renna Yanwastika Ariyana (PROSIDING SNAST, 2018)
Database design plays a very important role in the success and strength of an application. Factor normalization of design, non-duplication and optimization of memory usage become the main factor in assessment of a database. Research on location-based applications applied to mobile device system has been done by using object-based database and relational database, but the use of real time database has not been done. This study aims to build a real time database based (real time database) that will be applied to location-based applications. The method that will be used in this research is to design a database using Unified Modified Language (UML) by creating a Use Case, Class Diagram to explain the structure and activities of users and using Firebase to build a real time database and create an activity scenario for all actors involved. This research also builds a prototype of location-based applications for delivery and pick-up of goods within the scope of the Yogyakarta location. Location data is taken from Google Maps and uses several libraries from the Application Programming Interface (API). Testing of the database design is carried out with prototypes in the form of applications for delivery and pick-up of goods, where the inter location and pick-up is valid in real time on the officers. Database updates can be done in real time.